Research progress on the effects and mechanisms of tonifying traditional Chinese medicine ingredients in the treatment of Alzheimer's disease over the past five years - LAN Taijin; JIANG Lin; HONG Xiaohua; LIU Yiming; GUO Hongwei (Guangxi Yike Daxue xuebao)
With the intensification of population aging, the number of patients with Alzheimer's disease (AD) continues to rise. However, the exact pathogenesis of AD remains unclear, and existing drugs can only alleviate symptoms without providing a cure. Traditional Chinese medicine (TCM) holds that the pathogenesis of AD is closely related to kidney essence deficiency. Treatment often involves tonifying kidney essence, with frequent use of tonifying TCM ingredients in practice. With the introduction of modern scientific methods, the mechanisms of action of tonifying TCM ingredients in treating AD are gradually being revealed. This article systematically reviews the recent research progress on the use of TCM ingredients, including formulas, single ingredient, active parts and active ingredients in the treatment of AD, focusing on summarizing their complex mechanisms of action, including reducing Amyloid-beta (Aβ)/tau protein, neuroprotection and inhibition of neuroinflammation. Although significant progress has been made in the research on tonifying TCM ingredients for the treatment of AD, there are still many challenges in their clinical translation and application. In the future, it is necessary to further focus on tonifying TCM ingredients with clear efficacy, delve into their active ingredients, and elucidate their molecular mechanism networks to facilitate clinical translation and application. Meanwhile, systematic activity evaluation and screening of active parts are carried out for the understudied tonifying TCM ingredients in order to discover new therapeutic targets and provide more options for the treatment of AD.